1992
DOI: 10.1007/bf00311346
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of the coronary artery to pulmonary artery fistulas; a case of a large ruptured aneurysm

Abstract: Three patients were treated for coronary artery-pulmonary artery fistula. Each was asymptomatic due to a coronary artery fistula. There was one instance each of myocardial infarction, mitral stenosis and a large closed ruptured aneurysm including a thrombus. All the fistulas were comprised of several small plexiform arranged vessels. The left to right shunt ratio was approximately 8 percent or less. A surgical operation was performed to close the drainage orifice of the fistulas through pulmonary arteriotomy u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In aneurysmal fistulas, thrombus propagation from the aneurysm, distal emboli and rupture with hemopericardium, and/or cardiac tamponade are the most serious complications. 20 A review of the literature has revealed 14 cases with aneurysmal fistulas associated with rupture leading to cardiac tamponade and/or sudden death [1][2][3][4][5][6][7][8][9][10][11][12][13][14] wherein the majority of these patients were diagnosed ante mortem by coronary arteriography (Table 1). This was confirmed during surgical intervention, by pathologic examination or displayed at autopsy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In aneurysmal fistulas, thrombus propagation from the aneurysm, distal emboli and rupture with hemopericardium, and/or cardiac tamponade are the most serious complications. 20 A review of the literature has revealed 14 cases with aneurysmal fistulas associated with rupture leading to cardiac tamponade and/or sudden death [1][2][3][4][5][6][7][8][9][10][11][12][13][14] wherein the majority of these patients were diagnosed ante mortem by coronary arteriography (Table 1). This was confirmed during surgical intervention, by pathologic examination or displayed at autopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients had a dual (bilateral) origin and single termination of the fistula. 13,14 The termination into the right heart side was found in 12 and to the left heart side in only 1 of the patients. In 1 patient the termination was not reported.…”
Section: Clinical Presentationmentioning
confidence: 97%
See 2 more Smart Citations
“…7 there have been many reports of CAA concomitant with CAF, but those with rupture and cardiac tamponade are very rare. [8][9][10][11][12][13][14][15][16] We speculate that in the present case, congenital CAF were already extant and the CAA was secondary, probably as a result of the atherosclerotic changes of the walls of the CAF, because the patient did not have a history of chest trauma or have inflammatory symptoms similar to aortitis. It was rupture of the atherosclerotic aneurysm that resulted in cardiac tamponade.…”
Section: Discussionmentioning
confidence: 99%